“Manejo integrado de Strategus aloeus L. en el cultivo de palma africana (Elaeis guineensis)” - Massuh Castro, Eduardo Marllom (2022)
The extension of African palm cultivation in the production sectors in Ecuador, generates the accumulation of plant debris in several areas, referring to trunks of species in newly established crops or stipes of old plants in areas of renovation, favoring the proliferation of pests, Among these is Strategus aloeus L, which in its adult stage causes irreversible damage during the night, perforating the soil at the base of African palms less than 4 years old, affecting the root base and penetrating the stipe until it reaches the meristem. The affected African palm is susceptible to tipping as it grows, and in extreme cases may die, due to the total affectation of the root system and the meristem. The wounds caused allow the entry of phytopathogens that can cause diseases in the plant. There are management plans in which various technical control strategies are integrated, considering that prevention is the first control method to be taken into account. The information obtained was analyzed, synthesized and summarized to provide the reader with information on the integrated management of Strategus aloeus L. in African palm (Elaeis guineensis). Based on the above, it was determined that the typical symptoms of damage caused by the presence of Strategus aloeus L. begin with the appearance of deformations or death of the youngest leaves, generated by the effect of perforation of the apical meristematic system of growth of the plant. The revision and immediate control of Strategus aloeus adults inside the galleries is a very efficient practice. The different alternatives of integrated management of Strategus aloeus allow the reduction of popu